Urinary incontinence in primigravida: the neglected pregnancy predicament. (March 2016) - Abdullah, B.; Ayub, S.H.; Mohd Zahid, A.Z.; Noorneza, A.R.; Isa, Mohamad Rodi; Ng, P.Y.
Abstract: Objective: To determine the prevalence of urinary incontinence among primigravida in the third trimester, its risk factors and its effect to quality of life. Study design: This is a cross sectional study involving primigravida in their third trimester of pregnancy, who attended the Patient Assessment Centre of a tertiary referral hospital in Klang Valley from July 2012 to June 2013. The participants were chosen randomly using convenience sampling. A face-to-face interview and a review of their antenatal record were done by trained interviewers. Data on sociodemographic and risk factors were obtained followed by the International Consultation on Incontinence Questionnaire – Short Form (ICIQ-SF). The data was analysed using Statistical Package for Social Science version 20.0. Results: A total of 306 women were involved. The prevalence of urinary incontinence during third trimester was 34.3% (95%CI: 29.0, 39.7). Stress incontinence (64.8%) is the commonest followed by mixed incontinence (24.8%) and urge incontinence (6.7%). Childhood enuresis ( p  = 0.003) and previous history of urinary incontinence ( p  < 0.001) were significantly associated with urinary incontinence. More than 50 percent of women with urinary incontinence in the third trimester felt that it did not affect their daily activities at all. Only 10% of women felt greatly affected by this problem. Conclusion: Urinary incontinence is not uncommon among primigravida however many women did not feel that it affected their quality of life. Childhood enuresis and history of urinary incontinence were proven risk factors.